The Rat Thoracic Ultrasound protocol: scanning technique and normal findings - Piskovská, Anna; Kraszewska, Katarzyna; Hauptman, Karel; Jekl, Vladimír (Frontiers in Veterinary Science, 2024)
Respiratory diseases (especially pneumonia) are very common disorders in pet rats. The suspected diagnosis is mostly based on the clinical signs, thoracic auscultation, and thoracic radiography. However, the auscultation is insensitive in determining the severity of the disease, and radiographs are often unremarkable. Non-cardiac thoracic ultrasonography is increasingly used in veterinary medicine; however, it was not described in detail in rats. The thoracic ultrasonic examination was performed in 400 client-owned conscious pet rats. The rats were examined in the period from June 2023 to August 2023 in two veterinary clinics. Due to the small size of the animal, different anatomical considerations, different evaluation protocol, and to meet the optimal outcome of detailed thoracic ultrasound, a standard methodological protocol was developed, and the name RATTUS (RAT Thoracic UltraSound) was proposed. Typical signs of normal RATTUS were described (the bat sign, the lung sliding, A-lines, the abdominal curtain sign, the ski jump sign, the lung pulse, the seashore sign in M-mode, and the bamboo sign). The new evaluation of lung inflation symmetry by the substernal access was also described. The methodical approach presented, and normal findings description is proposed to be used for a standard/routine thoracic ultrasound examination in the pet rats.